Spectroscopic and antibacterial study of biochemically-derived silver nanoparticles. (2019) - Ntolia, Α.; Matisioudis, N.; Triantafillou, E.; Evangelopoulou, G.; Karachristou, V.; Rizos, E.; Karamanidou, T.; Tsouknidas, A.; Papadopoulos, D.; Tsipas, D.; Michailidis, N.; Aggeli, A.
Abstract: Silver nanoparticles (AgNPs) constitute a promising approach for the development of new antimicrobial systems. The major global concern about the emergence of bacterial strains resistant to widely used therapeutic agents for human infections has increased research for the discovery of new antimicrobial compounds as therapeutic alternatives. The aim of the present study was a preliminary investigation of the spectroscopic properties and inhibitory activity of silver nanoparticles on four reference gram negative and gram positive bacterial strains: Salmonella Typhimurium, Escherichia coli, Listeria monocytogenes and Staphylococcus aureus, at two different concentrations (103 and 106 cfu/ml) using cultivation media. The results confirmed that AgNPs absorb light in the visible area of the electromagnetic spectrum, as a fairly dominant and sharp peak appears at around 425 nm wavelength. These nanomaterials are shown here to be very effective antibacterial agents in both pathogen (Listeria, Salmonella) and non-pathogens (E.coli, Staphylococcus) microorganisms; furthermore the present study proves their efficacy against both Gram positive (Staphylococcus, Listeria) and Gram negative (E.coli, Salmonella) bacteria.